PANTELEIMON KYLISH. LIFE PARTS, SCIENTIFIC ACHIEVEMENTS AND MISCALCUTIONS - Осипенко, Іван (SWorldJournal, 2024)
The article examines the peculiarities of literary, scientific and public activity of P. Kulysh, as well as its influence on the Ukrainian intelligentsia and the general population of the inhabitants of the Ukrainian provinces of the Russian Empire. In pa